A new indentation model for sandwich circular panels with gradient metallic foam cores. (15th December 2015) - Mu, Lin; Cho, Chongdu; Zhao, Guiping; Xiao, Dengbao
Abstract: A new analytical model is presented to predict indentation behavior of the sandwich circular panel with gradient foam cores under a flat-end cylindrical indenter. In the model, a displacement field of the upper face sheet of the sandwich panel is assumed to be a cosine function and plateau stress of the gradient foam core varies with the mass density along the thickness direction of the sandwich panel. The sandwich panel is modeled as an infinite, isotropic, plastic membrane on a rigid-plastic foundation. The explicit solutions of the relation between the indentation force and maximum plastic regions of the upper face sheet are derived based on the principle of minimum work. The analytical results are validated using the finite element code ABAQUS ® . The influences of the gradient foam core on the maximum plastic region, the indentation force and the plastic strain energy of the sandwich panel are also investigated.